Manajemen kurikulum integratif sebagai karakteristik keilmuan perguruan tinggi islam - Zalfa, Syahgita (Maliki Interdisciplinary Journal, 2026)
The integrative curriculum is a key element of the scientific identity of Islamic Higher Education Institutions (PTKI), particularly UIN Maulana Malik Ibrahim Malang. This curriculum combines religious and general sciences into a unified educational system grounded in Islamic values and the principle of tawhid. This article explains the concept, principles, and implementation of the integrative curriculum, covering its planning, instructional practices, and evaluation processes. Integration is reflected not only in the development of study plans (RPS) but also in teaching methods, academic culture, and character formation through spiritual activities such as the ma’had and routine worship practices. The main objective of this curriculum is to produce graduates with the Ulul Albab profile—individuals who are intellectually competent, spiritually strong, and morally upright. The article also highlights several challenges, including differences in lecturers’ perspectives, uneven student understanding, and difficulties in adapting to digital technology. Despite these challenges, the integrative curriculum offers strong prospects for interdisciplinary research, innovative learning models, and improved graduate competencies. Strengthening lecturers’ capacities, effectively utilizing technology, and ensuring consistent implementation will support the integrative curriculum as a relevant and transformative foundation for Islamic higher education in the modern era.